2018
DOI: 10.1080/17405904.2018.1511440
|View full text |Cite
|
Sign up to set email alerts
|

‘I don’t think there is any moral basis for taking money away from people’: using discursive psychology to explore the complexity of talk about tax

Abstract: A 2018, ''I don't think there is any moral basis for taking money away from people': Using Discursive Psychology to explore the complexity of talk about tax' Critical Discourse Studies, vol. (In-Press), pp. (In-Press).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Cluster 3 is marked with the number 3 discussing social inequality legitimacy (Costa-Lopes et al, 2013). Cluster 4 is marked with number 4, which consists of three authors discussing the relationship between taxes and income inequality in a meritocracy (Carr et al, 2019). Cluster 5 discusses the path to power from the perspective of the corporate elite (Maclean et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Cluster 3 is marked with the number 3 discussing social inequality legitimacy (Costa-Lopes et al, 2013). Cluster 4 is marked with number 4, which consists of three authors discussing the relationship between taxes and income inequality in a meritocracy (Carr et al, 2019). Cluster 5 discusses the path to power from the perspective of the corporate elite (Maclean et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…As such, we thought it reasonable to include analysis of any texts that may contribute towards the constructions of what is socially 'known'. We were encouraged by the sense of opportunity and potential present in modern qualitative psychology research, particularly emboldened by the inclusions of radio (Carr, Goodman & Jowett, 2018) and televised debates (Goodman & Carr, 2017) as data, we began to consider how to approach I, Daniel Blake as a text. A concentration solely on the language spoken in a film seems to wilfully disregard the production choices made in the creation of a film; a decision that would make for an easier, but incomplete, analysis.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to this, rhetoric about individual responsibility legitimises the monitoring of unemployed people's search for employment. This use of individualistic discourse is also present in talk about tax where inequality is warranted as normal and the product of individual effort (Carr et al, 2019). Thus, individualistic ideology underlines talk about wealth inequality in society and positions individuals as responsible for their economic status.…”
Section: Discursive Social Psychology and The Construction Of The Super-rich In The Mediamentioning
confidence: 99%
“…Discursive and rhetorical approaches acknowledge the role of ideology in talk and its role in maintaining inequality in broadcast media (Carr, 2020). For example, previous discursive research has demonstrated how individualism is pervasive in talk about wealth, particularly when arguing against high tax rates (Carr et al, 2019). Such individualism presents wealth as being solely earned and ignores the role that the state (and public spending from taxation) has played in creating the economic conditions for their wealth.…”
Section: Discursive Social Psychology and The Construction Of The Super-rich In The Mediamentioning
confidence: 99%
See 1 more Smart Citation